The Impact of The Fourth Industrial Revolution on IIUM Student’s Motivation in Learning Islamic Education - Hafid Arif Saputra; Yunita Noor Azizah (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
The Fourth Industrial Revolution has impacted several fields, including education. Along with the rapid development of technology, the education sector is also progressing to encourage this development. Students need to stay motivated in learning Islamic education subjects and make good use of all the technology presented by the Fourth Industrial Revolution. This study aimed to describe the impact of the Fourth Industrial Revolution on students’ motivation in learning Islamic Education in Malaysia, especially among students at the International Islamic University Malaysia (IIUM). This study used a survey approach. The survey is in the form of a questionnaire in google form to make it easily accessed by students. The sample for this research consisted of 51 International Islamic University of Malaysia students with a random sampling technique. The researcher analyzed the data in-depth and concluded the impact of the Fourth Industrial Revolution on the motivation of IIUM students in learning Islamic Education. The result of this study is that phenomenon of Islamic education in the Industrial Revolution cannot be separated from gadgets and smartphones. Over half of the respondents, with a percentage of 71%, strongly said that students are very enthusiastic about using smartphones to learn through digital resources because it is easy for them to access information so that they can learn a lot about Islamic Education through smartphones or the internet. Thus, it can increase their motivation to learn Islamic Education. Furthermore, the Fourth Industrial Revolution has had a positive impact on IIUM Student’s Motivation in learning Islamic Education.